Effect of aerobic exercise on waist circumference in adults with overweight or obesity: A systematic review and meta‐analysis. (5th April 2022) - Armstrong, Alex; Jungbluth Rodriguez, Klaus; Sabag, Angelo; Mavros, Yorgi; Parker, Helen M.; Keating, Shelley E.; Johnson, Nathan A.
Summary: Excess visceral adiposity contributes to elevated cardiometabolic risk, and waist circumference is commonly used as a surrogate measure of visceral adipose tissue. Although regular aerobic exercise is known to improve abdominal obesity, its effect on waist circumference is unclear. A systematic review and meta‐analysis was performed to determine (1) the effect of aerobic exercise on waist circumference in adults with overweight or obesity; (2) the association between any change in waist circumference and change in visceral adipose tissue and/or bodyweight with aerobic exercise interventions; and (3) if reductions in waist circumference with exercise are moderated by clinical characteristics or components of aerobic exercise prescription. Twenty‐five randomized controlled trials (1686 participants) were included. Regular aerobic exercise significantly reduced waist circumference by 3.2 cm (95% confidence interval [CI] −3.86, −2.51, p  ≤ 0.001) versus control. Change in waist circumference was associated with change in visceral adipose tissue ( β  = 4.02; 95% CI 1.37, 6.66, p  = 0.004), and vigorous intensity produced superior reduction (−4.2 cm, 95% CI −4.99, −3.42, p  < 0.0001) in waist circumference compared with moderate intensity (−2.50 cm, 95% CI −3.22, −1.79, p  = 0.058). These findings suggest regular aerobic exercise results in modest reductions in waist circumference and associated visceral adipose tissue and that higher intensity exercise may offer superior benefit to moderate intensity.